PENGEMBANGAN GAME LABIRIN EDUKATIF PADA MATERI BAHAYA NARKOTIKA, PSIKOTROPIKA, DAN ZAT ADIKTIF MATA PELAJARAN PJOK KELAS V SD - Arsyad, Khairul; Pratiwi, Rahmi; Kurnia, Reni; Alfahani, Khairul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Drug abuse (NAPZA) among Indonesian adolescents remains a critical issue, necessitating more effective preventive education through formal schooling. This study aims to develop an Educational Maze Game (Game Labirin Edukatif) on the topic of the dangers of Narcotics, Psychotropics, and Addictive Substances (NAPZA) for Class V elementary school students in Physical Education, Sports, and Health (PJOK) subject. The research used the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). Trial subjects included one material expert validator (PJOK teacher), two media expert validators from Educational Technology lecturers at UNP, and 20 students of Class V at UPTD SD Negeri 03 Andiang as field trial subjects. Data collection used material validation questionnaires, media validation questionnaires, and student practicality response questionnaires. Results showed material validity at 90% ("Very Valid"), media validity at 94.28% ("Very Valid"), and student practicality at 94.48% ("Very Practical"). The Educational Maze Game developed using Visual Studio Code is valid and practical as an innovative learning medium to improve student motivation, active engagement, and understanding of NAPZA dangers in PJOK learning.